From lifetime to evolution: timescales of human gut microbiota adaptation - Quercia, Sara; Candela, Marco; Giuliani, Cristina; Turroni, Silvia; Luiselli, Donata; Rampelli, Simone; Brigidi, Patrizia; Franceschi, Claudio; Bacalini, Maria Giulia; Garagnani, Paolo; Pirazzini, Chiara (Frontiers in Microbiology, 2014)
Human beings harbor gut microbial communities that are essential to preserve human health. Molded by the human genome, the gut microbiota is an adaptive component of the human superorganisms that allows host adaptation at different timescales, optimizing host physiology from daily life to lifespan scales and human evolutionary history. The gut microbiota continuously changes from birth up to the most extreme limits of human life, reconfiguring its metagenomic layout in response to daily variations in diet or specific host physiological and immunological needs at different ages. On the other hand, the microbiota plasticity was strategic to face changes in lifestyle and dietary habits along the course of the recent evolutionary history, that has driven the passage from Paleolithic hunter-gathering societies to Neolithic agricultural farmers to modern Westernized societies.